Silagem pré-secada de aveia branca e aveia preta emurchecidas com doses de glifosato - Bueno, Antonio Vinicius Iank (2015)
This experiment aimed to evaluate the effect of wilting White Oat (Avena sativa L. cv. Corona) using glyphosate (N-fosfometilglicine) on the nutritional quality, fermentation characteristics, aerobic stability and dry matter recovery of the resulting silages. The dosages used were 0 (control), 500, 750, 1000 and 1250 mL/ha with 4 replicates per treatment in a completely randomized design. Statistical procedures for data analyzes were performed by Bayesian Inference. The application of glyphosate increased the dry matter in treated silages compared to the control, at doses 500, 750 and 1000 ml/ha, which reflected on the dry matter recovery rate, being reported maximum recovery (93.44 %) if glyphosate was applied at the rate of 864.2 ml/ha. Quadratic effect was observed for neutral detergent fiber, where the lowest value reported (642.8g/kg of dry matter) would be obtained if the application of the product were in the order of 1141.32 ml/ha. Hemicellulose showed negative linear behavior, for each increase of 1 ml of glyphosate was observed a reduction of the fraction in the amount of 0.05 g / kg of dry matter. The use of glyphosate also reduced crude protein (0.04 g / kg of dry matter per 1 ml of glyphosate applied) as for pH where the drop would be on the order of 0.01 per ml of glyphosate. Regarding the aerobic stability did not show significant results for most treatments, being able to highlight the silage resulting from the application of 750 ml / ha of glyphosate, which had, in the mean values, reduction of maximum temperature values (28.14ºC), sum of temperatures (234ºC) and average temperatures (26.01ºC) and longer aerobic stability (74 hours). The use of glyphosate was able to change the fermentation profile of the resulting silage when compared to untreated silages, and the observed effects presented quadratic behavior. The point of minimum concentration of butyric acid (0.34% of dry matter) would be observed if the glyphosate was applied at the rate of 900.8 ml/ha. As for the butanediol (0.73% DM) and formic acid (0.18% dry matter) would increase the levels of these metabolites when the product was used in doses of 861.7 and 874.3 ml/ha, respectively. The minimum concentration of ethyl-lactate (146.6 g/kg dry matter) was obtained glyphosate when applied in the order of 808.55 ml / ha. When used in a dose of 916.51 ml/ha glyphosate raise the concentration of ammonia to total nitrogen at 5%. Thus, analyzing the results of this study it is recommended the use of glyphosate at a dose of 500 ml/ha to wilt the white oat for silage making.